2020
DOI: 10.1101/2020.12.04.411694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Translational Readthrough Tunes Functions of the Traffic Jam Transcription Factor

Abstract: SummaryTranslational readthrough (TR) occurs when the ribosome decodes a stop codon as a sense codon, resulting in two protein isoforms synthesized from the same mRNA. TR is pervasive in eukaryotic organisms; however, its biological significance remains unclear. In this study, we quantify the TR potential of several candidate genes in Drosophila melanogaster and characterize the regulation of TR in the large Maf transcription factor Traffic jam (Tj). We used CRISPR/Cas9 generated mutant flies to show that the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…One possibility is translational readthrough (63)(64)(65)(66)(67), or alternatively the bacteria could be inserting selenocysteine into these proteins in lieu of the stop codon. dgcQ mutations have been observed in at least six different strains of EAEC in the same specific pattern observed in S. flexneri 2457T, with an insertion of stop codon at 312 amino acid position and adjacent methionine (AUG) at 314 codon; this suggests that, like dgcE, the dgcQ adaptation is not unique to this specific Shigella strain (62).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is translational readthrough (63)(64)(65)(66)(67), or alternatively the bacteria could be inserting selenocysteine into these proteins in lieu of the stop codon. dgcQ mutations have been observed in at least six different strains of EAEC in the same specific pattern observed in S. flexneri 2457T, with an insertion of stop codon at 312 amino acid position and adjacent methionine (AUG) at 314 codon; this suggests that, like dgcE, the dgcQ adaptation is not unique to this specific Shigella strain (62).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found ribosome footprints also on the 3′ UTR of certain transcripts, such as Synapsin (Figure 3C). Stop-codon readthrough has been reported to be more frequent in neurons than in other cell types (49)(50)(51). Because the readthrough events extend the protein C-terminus, its regulation can add yet another layer of cell-type diversity (14,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies involving Ribo-Seq of animal tissues and organs revealed organspecific differences in translation efficiency and elongation speed [12][13][14][15]. Other findings revealed different tRNA repertoires and codon usage in different tissues [16,17], as well as peculiar features like readthrough rate [18]. However, to which extent the tissue-specificity of gene expression is determined at the translation level is still a poorly resolved issue.…”
Section: Recentmentioning
confidence: 99%